GingaForAll: linha de Produtos do Middleware Ginga - Pereira, Lucas Silva (2010)
Many challenges have been imposed on the middleware to support applications for digital TV because of the heterogeneity and resource constraints of execution platforms. In this scenario, the middleware must be highly configurable so that it can be customized to meet the requirements of applications and underlying platforms. This work aims to present the GingaForAll, a software product line developed for the Ginga - the middleware of the Brazilian Digital TV (SBTVD). GingaForAll adds the concepts of software product line, aspect orientation and model-driven development to allow: (i) the specification of the common characteristics and variables of the middleware, (ii) the modularization of crosscutting concerns - both mandatory and concepts variables - through aspects, (iii) the expression of concepts as a set of models that increase the level of abstraction and enables management of various software artifacts in terms of configurable models. This work presents the architecture of the software product line that implements such a tool and architecture that supports automatic customization of middleware. The work also presents a tool that implements the process of generating products GingaForAll